Exposure Time Dependence of Operators’ Head Entrance Air Kerma in Interventional Radiology Measured by TLD-100H Chips - Rocco Mottareale; Francesco Manna; Patrizio Antonio Carmosino; Francesco Fiore; Marco Correra; Salvatore Stilo; Luca Tarotto; Mariagabriella Pugliese (Sensors, 2025)
Interventional radiology offers minimally invasive procedures guided by real-time imaging, reducing surgical risks and enhancing patient recovery. While beneficial to patients, these advancements increase occupational hazards for physicians due to chronic exposure to ionizing radiation. This exposure raises health risks like radiation-induced cataracts, cardiovascular disease, and cancer. Despite regulations like the European Council Directive 2013/59/EURATOM, which sets limits on whole-body and eye lens doses, no dose limits exist for the brain and meninges, since the brain has traditionally been considered a radioresistant organ. Recent studies, however, have highlighted radiation-induced brain damage, suggesting that meningeal exposure in interventional radiology may be underestimated. This study evaluates the entrance air Cumulative mean annual entrance air kerma to the skullull during interventional radiology procedures, using thermoluminescent dosimeters and controlled exposure simulations. Data were collected by varying the exposure time and analyzing the contribution to the entrance air kerma on each side of the head. The results indicate that, considering the attenuation of the cranial bone, the absorbed dose to the brain, obtained by averaging the head entrance air kerma for the right, front, and left sides of the operator’s head, could represent 0.81% to 2.18% of the annual regulatory limit in Italy of 20 mSv for the average annual effective dose of exposed workers (LD 101/2020). These results provide an assessment of brain exposure, highlighting the relatively low but non-negligible contribution of brain irradiation to the overall occupational dose constraint. Additionally, a correlation between entrance air kerma and the Kerma-Area Product was observed, providing a potential method for improved dose estimation and enhanced radiation safety for interventional radiologists.